Presowing Treatment of Black Wattle (Acacia mearnsii De Wild.) and Australian Blackwood (Acacia melonoxylon R. Br.) Seed. - Gupta, B. N.; Thapliyal, R. C. (Indian Forester, 1974)
Seeds of Black wattle and Australian blackwood are hardcoated and when sown in the laboratory for routine germination test or in the nursery without suitable pretreatment result in poor germination. Methods in vogue for the pretreament of these seeds prescribe steeping seeds in hot water for periods varying from 12 to 24 hours or stirring in concentrated sulphuric acid for 1 hour. Present investigation indicates that 5 minutes steeping of seeds in hot water is sufficient to break the dormancy of hard coated seeds of these species.